Symmetries or Asymmetries: How MSCI Index Advanced European Markets’ Exchange Rates Respond to Macro-Economic Fundamentals - Mosab I. Tabash; Muhammad AsadUllah; Quratulain Siddiq; Marwan Mansour; Linda Nalini Daniel; Mujeeb Saif Mohsen Al-Absy (Economies)
The purpose of this study is to find symmetries and asymmetries in the exchange rate and macroeconomic fundamentals of advanced European markets, namely Denmark, the Euro Area, and United Kingdom, for the period of 2011 to 2022 via application of the NARDL technique. The findings reveal that interest rate affects DKK exchange rate asymmetrically in the long and short run, whereas money supply affects it in the short run. Foreign reserves are found to be helpful for all three currencies in stabilizing the exchange rate. A decline in gold price weakens GBP, DKK, and EUR in the long run. Previous studies suggest that the existence of asymmetrical relationships justifies the selection of NARDL for empirical analysis. This study makes a contribution to the existing literature, as it proves that forecasting via NARDL is also robust for analysis. The findings have significant policy implications for financial applications.